Comparative Study of Regular Teachers’ Special Education Pedagogy Competence Level in Elementary and Senior High Inclusive School - Tias Martika; Abdul Salim (Department of Special Education, 2017)
Comparative Study of Regular Teachers’ Special Education Pedagogy Competence Level in Inclusive School Elementary and Senior High School Level. In general, this research aims to determine regular teachers’ special education pedagogy competence level in the level of elementary and senior high inclusive school. Subject in this research was 38 regular teachers in elementary inclusive school and 45 regular teachers in senior high inclusive school. Data was collected through questionnaire. Data was analyzed by using normality test, homogeneity test, and t-independent test. Result of this research showed that data from both variables was normal, homogeny, and the average score of regular teachers’ pedagogy competence in elementary school is 61.5 while the average score of regular teachers’ pedagogy competence in senior high school is 48.78. It can be concluded that regular teachers’ special education pedagogy competence level in elementary school is higher than in senior high school.